Noise and Signal in Debates among Classical Economists: A Reply - Samuelson, Paul A. (Journal of Economic Literature, 1980)
It is high praise when so expert a * scholar as Samuel Hollander (1980) hails my canonical classical model (1978) as likely to become locus classicus for the next generation of textbook writers. Like Fletcher I care not who makes a nation's laws if I can shape its textbook writers' songs. But with power comes responsibility. I must weigh and respond to the doubts Dr. Hollander raises about some positions I took in the three-seventeenths of my positivistic text that digresses to interpret particular historical controversies. I shall be brief and deal only with most essential points.